Frailty Measures in Patients Listed for Lung Transplantation. Issue 5 (19th May 2021) - Montgomery, Elyn; Newton, Phillip J.; Chang, Sungwon; Peng, Wenbo; Jha, Sunita R.; Wilhelm, Kay; Macdonald, Peter S.; Malouf, Monique
Abstract : Background: The study aimed to determine whether the addition of cognitive impairment, depression, or both, to the assessment of physical frailty (PF) is associated with the risk of lung transplant (LTX) waitlist mortality. Methods: Since March 2013, all patients referred for LTX evaluation underwent PF assessment. Cognition was assessed using the Montreal Cognitive Assessment and depression assessed using the Depression in Medical Illness questionnaire. We assessed the association of 4 composite frailty measures: PF ≥3 of 5 = frail, cognitive frailty (CogF ≥3 of 6 = frail), depressive frailty (DepF ≥3 of 6 = frail), and combined frailty (ComF ≥3 of 7 = frail) with waitlist mortality. Results: The prevalence of PF was 78 (22%), CogF 100 (28%), DepF 105 (29%), and ComF 124 (34%). Waitlist survival in the non-PF group was 94% ± 2% versus 71% ± 7% in the PF group ( P < 0.001). Cox proportional hazards regression analysis demonstrated that PF (adjusted hazard ratio [HR], 4.88; 95% confidence interval [CI], 2.06-11.56), mild cognitive impairment (adjusted HR, 3.03; 95% CI, 1.05-8.78), and hypoalbuminemia (adjusted HR, 0.89; 95% CI, 0.82-0.97) were independent predictors of waitlist mortality. There was no significant difference in the area under the curve of the 4 frailty measures. Conclusions: The addition of cognitive function and depression variables to the PF assessment increased the number of patients classified as frail. However, the addition of these variables does not strengthen the association with LTX waitlist mortality compared with the PF measure.